The lion and the mouse : an Aesop fable - Watts, Bernadette; Aesop (New York : Scholastic, 2001)
A tiny mouse helps a mighty lion, who had once showed him mercy, escape from a trap.
"First published in Switzerland under the title Der Lowe und die Maus"--copyright page.
K
540
K
AD
Keywords: Fables; Folklore